Produksi Garam Rakyat Berbasis Tuf Geomembran Di Kecamatan Samatiga Kabupaten Aceh Barat - Mahendra Mahendra (Jurnal Marine Kreatif, 2017)
Devotion is aimed to increase production salt in samatiga. Problems when it was a necessity of a salt with the quality of both in indonesia still rely on imported from foreign. It was because the qualities of a salt was still a lot of those managed in a traditional that is by using the light of the sun directly. To increase production salt needed latest technology able to return production land damaged quickly.Technology TUF geomembrane is technology is very effective used to a reservoir.Besides geomembran, the use of threaded filter used to fasten the process of crystallization will be quickly and the qualities of a salt whiter and not need to laundering salt.Produce a salt with that is only enough 7 to 10 the day the process drying be crystallization with good qualities.